Stakeholders Inception Meeting: Tanzania Seed Sector Development Strategy (TSSDS) - Rweyemamu, M. R.; Mruma, T.; Nkanyani, S. (International Water Management Institute (IWMI), 2024)
On November 14, 2023, the Ministry of Agriculture's Department of Crops Development (DCD) convened an Inception Meeting on the Seed Sector Development Strategy (SSDS) at the Gran Melia Hotel in Arusha, Tanzania supported by USAID through the SERA BORA project and CGIAR's Ukama Ustawi initiative. Attended by a diverse array of stakeholders, the meeting aimed to initiate discussions on the SSDS, marking a crucial step towards shaping a comprehensive and impactful strategy for Tanzania's seed sector.